Solid foundations - growth and ethical teaching - Mizusaki, Jorge (Scientific Journal of the Foot & Ankle, 2018)
In this edition, we have the opportunity to offer our readers a moment of which we are very proud. What started out as Revista ABTPé is now the Scientific Journal of the Foot and Ankle, and it is now available in electronic format, for the global scientific community. The work is the result of the combined efforts of a fantastic generation of professionals who have promoted the development of medicine and surgery of the foot and ankle in Brazil, and also in South America. Nowadays, knowledge has no boundaries, but the scientific language is still mostly linked to the English language. Our journal is in line with this global trend. We also highlight the important influence of our masters, who blazed arduous trails in search of scientific knowledge in foreign lands, bringing, and demanding the rigor of scientific training, and applying teaching methods that have evolved over time, while still preserving the ethical essence of research, teaching, and the art of medical activity. In these times of rapid change, and upheavals in the medical climate, education, and technical knowledge, it is enriching to recognize the essence of the teachers. We have reached a new level. Good reading.